Elemental analysis and IR band characteristics of α-Fe2O3 and BaFe12O19 steel waste product based - Che Muda, Nor Nadhirah; Azis, Raba’ah Syahidah; Shaari, Abdul Halim; Hassan, Jumiah; Sulaiman, Sakinah (Malaysian Solid State Science and Technology Society, 2016)
This project focused on the elemental analysis and IR band characteristic of -Fe2O3 derived from recycled steel waste product. The steel waste flakes were ball milling for several hours to form a fine powder. The steel waste powder had been purified by using impurity separation technique and magnetic separation technique. The purified steel waste powder then oxidized at 500 oC to form hematite (Fe2O3). The hematite were used to synthesize BaFe12O19 by using salt-melt method. The samples were characterized using X-ray Fluorescence (XRF), Fourier Transform Infrared spectroscopy (FTIR), X-ray diffraction (XRD) and energy-dispersive X-ray analysis (EDAX). The XRF and FTIR results show the formation of Fe2O3, the IR characteristic bands of Fe2O3 and single phase BaFe12O19 is obtained from recycled steel waste product.